Between the decadent movement and the Criollismo (Regionalism movement): the case of «Los ojos de Judas» (The eyes of Judas) by Abraham Valdelomar - Valenzuela Garcés, Jorge (2016)
In this article we study the complex relationships between certain Decadent components, typical characteristics of the modernist inheritance, and those of criollista poetry, both present in «Los ojos de Judas» by Abraham Valdelomar. We postulate that, in the case of this story, it is possible to identify a heterogeneous narrative to aim to be national from the local reinvindication; but, in turn, does not abandon the characteristics of Decadent modernism such as exploration of the evil, disease, and the questioning of Christian values. An analysis of this story from the comparison of the decadent and criollismo poetry is performed, in addition, to an approach of the text that relies on the analysis of the narrative programme and the intertextual relationships that are set in the story.